AN ANALYSIS OF ERRORS IN THE TRANSLATION OF "KINGDOM COME", A COMIC BOOK WRITTEN BY ALEX ROSS AND MARK WAID - Agung Kurnia, - (2006)
This research paper focuses on investigating errors in the process of translating English comic books into Indonesian. It also investigates the strategies applied by the translator in translating those books. A linguistics error analysis is then applied to answer the questions of what errors the translator make in translating English comic books into Indonesian; what the possible causes are; and what possible solutions can be carried out to solve the problems. The method that the writer uses in conducting the research is qualitative descriptive method. It allows the writer to make a systematic and factual description about the gained data. The result of the study shows that omissions and incorrect choice of words are the most frequent forms of errors found in the texts, in this case translating English comic books into Indonesian. The other errors found in the texts are words that are out of order, grammatical errors, spelling mistakes, general errors and broader general errors. The possible causes for those errors are as a result of the lack of vocabulary mastery, inaccuracy or the translator were unfamiliar with the word to be translated, lack of knowledge of appropriate diction to use, the lack of grammatical meaning and misinterpretation of meaning, LI interference, slip of pen, lapses, overgeneralization, misunderstood the meaning of the sentence thoroughly, ignorance of rule restrictions and some psychological factors. The causes are not necessarily derived only from one of them, but it can also as a result of the combination of some factors at the same time. From eight strategies found in the books; reduction, expansion, shift, transference, naturalization, through-translation, synonymy, and cultural equivalent, it appears that the most frequently used strategy is the translation by reduction strategy. The range of each strategy application differs from one another due to their conventions and limitations. From all the process of analysis and result of the study, the writer would like to propose some suggestions. First, the writer suggests that a translator should always try to extend his/her knowledge and improve it. The second suggestion is for the lecturers to try to discuss new and different texts in practicing translation theory. The last suggestion is for the future researchers. The writer hopes that they could have a better research and can obtain some information related to the field from this paper.